Indirect determination of nitrate ions in vegetables by atomic absorption spectrophotometry - Yilmaz, Feride; Islimyeli, Sezen; Ozgur, Mahmure; Canlica, Mevlude (WALTER DE GRUYTER GMBH, 2007)
The nitrate ions in the vegetables were determined by indirect atomic absorption spectrophotometry (AAS). The method is based on the reduction of the nitrate ions by boiling with metallic cadmium granules in 0.1 N hydrochloric acidic medium under carbondioxide atmosphere for 30 min under reflux. Released cadmium (11) ions were measured by AAS at 228.8 nm and the amount of the nitrate ion was calculated. The calibration curve was plotted between absorbance values and cadmium concentrations in the range of 0.362-1.810 mu g/mL Cd2+ (0.1-0.5 mu g/mL NO3-). The regression equation of the calibration curve was found to be A= 0.1771C+0.0135 (r=0.9999). The vegetable samples (potato, tomato, chard, radish and carrot) were analysed by the proposed method and standard addition technique as a reference method. Statistical comparison of the results showed that the assay results obtained by the two methods were in good agreement.
Keywords: nitrate ion; vegetables; atomic absorption spectrophotometry; indirect determination; NITRITE; PRODUCTS; SAMPLES; Chemistry